APPLICATION OF INNOVATIVE TECHNOLOGIES IN PRIMARY SCHOOL AND ITS TASKS IN PERSONALITY FORMATION - Rakhimova , Mehribon Abdukholisovna (Educational Research in Universal Sciences, 2023)
This article discusses the requirements for the personal results of students who have mastered the basic educational program of the educational standard of basic general education. Requirements for personal results include the development of moral feelings, goodwill and emotional and moral sensitivity, the development of understanding and empathy for the feelings of other people, the development of cooperation skills with adults and peers in various social situations, conflicts and controversial theoretical situations, information about ways out of situations.